Clinical and Diagnostic Considerations for Atypical, Adult Onset Presentation of Chronic Recurrent Multifocal Osteomyelitis (CRMO) - Stacey Mahady; Amit Ladani (Case Reports in Rheumatology)
Chronic recurrent multifocal osteomyelitis (CRMO) is the most severe form of chronic nonbacterial osteomyelitis (CNO) and is a rare autoinflammatory bone disorder that mostly affects children and adolescents. CRMO is a diagnosis of exclusion, resulting in often-delayed diagnosis with over one year on average from onset of symptoms to time of diagnosis. Initial diagnosis is rare in adults and previously undocumented in the elderly (age greater than 65). We highlight a case of a 74-year-old elderly Caucasian female with a history of palmoplantar pustular psoriasis who presented with pelvic and hip pain. Imaging findings included multiple bony lesions on x-rays, increased uptake in the left side of the pelvis, ileum, proximal sternum, and bilateral medial clavicles on nuclear bone scan. Bone biopsy histologic results of marrow fibrosis and plasma cell infiltrate indicative of chronic inflammation lead to the diagnosis of CRMO. This case highlights that while CRMO is typically a disease with childhood onset, it, while rare, can also present in adults and now has presented in the elderly, remaining an important part of the differential diagnosis of bone pain in adults and the elderly in addition to infectious osteomyelitis and malignancy when imaging reveals multiple bony lesions. This in turn will facilitate the reduction of unnecessary medical treatment and antibiotics.